The gendered society - Kimmel, Michael S. (Oxford University Press, 2000)
They say that we come from different planets (men from Mars, women from Venus), that we have different brain chemistries and hormones, and that we listen, speak, and even define our morals differently. How is it then that men and women live together, take the same classes in school, eat the same food, read the same books, and receive grades according to the same criteria? In The Gendered Society, Michael S. Kimmel examines our basic beliefs about gender, arguing that men and women are more alike than we have ever imagined. Kimmel begins his discussion by observing that all cultures share the notion that men and women are different, and that the logical extension of this assumption is that gender differences cause the obvious inequalities between the sexes. In fact, he asserts that the reverse is true--gender inequality causes the differences between men and women. Gender is not simply a quality inherent in each individual--it is deeply embedded in society's fundamental institutions: the family, school, and the workplace. The issues surrounding gender are complex, and in order to clarify them, the author has included a review of the existing literature in related disciplines such as biology, anthropology, psychology and sociology. Finally, with an eye towards the future, Kimmel offers readers a glimpse at gender relations in the next millennium. Well-written, well-reasoned and authoritative, The Gendered Society provides a thorough overview of the current thinking about gender while persuasively arguing that it is time to reevaluate what we thought we knew about men and women.